(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
The social changes in Eastern Europe became a current research topic especially after the fall of the socialist system and during the transformation of the former socialist societies into Western Europe type democracies. At the same time, these societies are said to be changing societies, transitioning societies, post-socialist societies etc. In spite of the tendency to copy the western European democracies, the eastern European countries are still seen by others as something different.